2023
DOI: 10.1007/s10787-023-01169-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin C on respiratory, allergic and immunological diseases: an experimental and clinical-based review

Abstract: Vitamin C is used in modern medicine supplements for treatment of various disorders associated with oxidative stress, inflammation and immune dysregulation. In this review article, experimental and clinical results regarding the effects of vitamin C on respiratory immunologic, and allergic diseases are reviewed. Various databases and appropriate keywords are used to search the effect of vitamin C on respiratory diseases until the end of May 2022. Books, theses and articles were included. These studies assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…In the pathogenesis of childhood asthma, Lung helper T cell 2 (Th2) causes airway hyper-responsiveness and remodeling through inflammatory pathways [ 38 ]. Supplement with VD and VC increases in the production of pro-inflammatory cytokines, and can reduce respiratory infections, which suggested they can enhance the immune response, thereby reducing the risk of asthma [ 10 , 39 ]. However, further studies are needed to make these causal relationships clearer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pathogenesis of childhood asthma, Lung helper T cell 2 (Th2) causes airway hyper-responsiveness and remodeling through inflammatory pathways [ 38 ]. Supplement with VD and VC increases in the production of pro-inflammatory cytokines, and can reduce respiratory infections, which suggested they can enhance the immune response, thereby reducing the risk of asthma [ 10 , 39 ]. However, further studies are needed to make these causal relationships clearer.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins are obtained from the daily diet and play important roles in maintaining normal physiological functions of the human body, and take part in the occurrence and development of a variety of diseases [ 9 ]. Anti-oxidative vitamins, such as vitamin C (VC) and vitamin E (VE), have anti-inflammation effects and are involved in the oxidative stress caused by scavenging reactive oxygen species (ROS), and thus may reduce the risk of asthma [ 10 , 11 ]. On the other hand, dietary intake of a number of vitamins may be associated with an increased risk of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C acts as antioxidant at low doses (30-100 mg/kg) and pro-oxidant at high doses (1000mg/kg) (49). The LD50 of vitamin C is 11,900mg/kg in rats (50). 2g/kg of glucose was given simultaneously with 1000mg/kg of vitamin C and 20mg/kg of 5,7-dimethoxycoumarin, in Rats 24-25.…”
Section: Methodsmentioning
confidence: 99%
“…A meta data analysis showed that in mouse allergic models, administration of high vitamin C doses results in less severe inflammation with a shift from Th2 towards Th1 cytokine profiles, namely increased IFNγ and less IL-4 production [ 43 ]. The treatment with vitamin C also reduced the production of pro-inflammatory cytokines like TNFα and IL-1 through ROS-dependent inhibition of NF-κB [ 43 ].…”
Section: Role Of Vitamin C In Th Cell Differentiationmentioning
confidence: 99%
“…A meta data analysis showed that in mouse allergic models, administration of high vitamin C doses results in less severe inflammation with a shift from Th2 towards Th1 cytokine profiles, namely increased IFNγ and less IL-4 production [ 43 ]. The treatment with vitamin C also reduced the production of pro-inflammatory cytokines like TNFα and IL-1 through ROS-dependent inhibition of NF-κB [ 43 ]. In addition to the modulation of pro-inflammatory cytokines, vitamin C also promoted the secretion of the immunosuppressive cytokine IL-10 by dendritic cells (DCs), which in turn inhibits the production of pro-inflammatory cytokines [ 44 ].…”
Section: Role Of Vitamin C In Th Cell Differentiationmentioning
confidence: 99%